Kearifan Lokal Petani Padi di Desa Klungkung, Kecamatan Sukorambi Kabupaten Jember dalam Menyikapi Kebijakan Pengurangan Subsidi Pupuk - Prayugingsih, Henik; Muliasari, Risa Martha; Muliasari, Anisa Nurina (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Decreasing of subsidy fertilizer policy caused high cost farming, because subsidy fretilizer is limited so farmers must buy by market price when they want more. In order to get enough income for fulfil family needs, farmers at Klungkung Village, Sub District of  Sukorambi, Jember Regency have to find a way for overcome this policy.  The choosen alternative is made liquid organic fertilizer by themselves as local wisdom to apply healthy paddy  farming, that is apply organic fertilizer beside inorganic fertilizer.  This study aimed to analyze: (1)  local wisdom ; (2) impact of decreasing of subsidy fertilizer policy to paddy farming production; dan (3) impact of decreasing of subsidy fertilizer policy to paddy farming income at  Klungkung Village, Sub District of  Sukorambi, Jember Regency. Study was done in reany planting season  2022-2023. Sampel was determined by Convenience Sampling, with 25 farmers of helathy paddy and 25 farmer of convensioanl paddy, which just use inorganic fertilizer for their plant. Descriptive analilysis, income anaysis and multiple regression analysis were used for reaching thoose goals. The result were: (1) local wisdom at Klungkung Village, Sub District of  Sukorambi, Jember Regency have for overcome decreasing of subsidy fertilizer policy is using “gotong royong” institution to make  liquid organic fertilizer by themselves to apply healthy paddy  farming by using potencia lnature  resouches around them.  “Gotong royong” is an old institution means working together for reaching benefit together; (2) healthy paddy farming income was Rp 19.031.278, higher than convencional paddy farming by Rp 22.311.573/ha and  significant at 5% test level; (3) healthy paddy farming production  was 1,19  higher  than convencional paddy farming and significant at 5% test level.